Engineering Education Quality Assurance : A Global Perspective - Patil, Arun (Boston, MA : Springer-Verlag US, 2009., 2017)
Engineering Education Quality Assurance: A Global Perspective provides a world-wide view of the history and the current conditions of Engineering Education Quality Assurance. This book provides the first wide-ranging picture of Quality Assurance schemes from essentially every continent and the issues related to their development and implementation. In addition, a generic Engineering Education Quality Assurance Model is described that synthesizes all of the extant approaches and provides a structure for future development.